ANALISA DINAMIKA KERJASAMA KOTA MEDAN-GWANGJU DALAM KERANGKA SISTER CITY PADA TAHUN 2017-2021 - Siregar, Rifqi Mulya Nauli; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study analyzes the Dynamics of Medan-Gwangju City Cooperation within the Sister City Framework in the 2017-2021 period. The Medan City Government has carried out this collaboration since the signing of the Memorandum of Understanding (MoU) in 1997. International cooperation which generally involves a state has been transformed in terms of actors so that it involves sub-state actors as actors in international relations, this is included in the phenomenon of paradiplomacy as an effort advancing regional potential in accordance with the mandate of regional autonomy policy. In the long course of cooperation involving the two sub-state or regional government actors, of course there are dynamics in the relationship and problems that occur in the cooperative relationship. This research was using qualitatively descriptive using several methods in data collection, including interviews, observations, and literature studies from books, journals, websites, and documents related to this collaboration. This study uses the perspective of liberalism and paradiplomacy theory. The results of this paper show how in accordance with the theory of paradiplomacy, the Medan City Government seeks to maximize the potential of the area contained in the City of Medan. However, in an effort to maximize the potential of the area which is manifested in the form of cooperation within the sister city framework, there are dynamics that occur during a cooperative relationship as well as problems and potential for cooperation that have not been optimized and then this paper can be used as material for consideration of City Government policy making. Medan in carrying out international cooperation as a sub-state actor. Keywords: Dynamics, Sister City, Paradiplomacy, Local Government, Medan City, Gwangju City, Momerandum of Understanding.